Predictors of treatment abandonment for patients with pediatric cancer at Indus Children Cancer Hospital, Karachi, Pakistan. Issue 2 (27th September 2017) - Siddiqui, Durr‐e‐Fatima; Ashraf, Muhammad Shamvil; Iftikhar, Sundus; Belgaumi, Asim F.
Abstract: Background: Abandonment of treatment is one of the toughest challenges to deal with in pediatric oncology. It leads to unnecessary mortality and morbidity in patients from low‐ and middle‐income countries. Procedure: The objective of our retrospective study was to determine the prevalence and predictors for abandonment among children with cancer at our hospital in Karachi, Pakistan. We analyzed data on patients younger than 18 years, diagnosed with any malignancy between November 2014 and May 2016. Results: From a total of 821 patients, one hundred and eighty‐two (22.2%) patients abandoned treatment at various stages, 92 (11.2%) patients did not initiate treatment at all, and the remaining 90 (11.0%) left during treatment. The gender ratio at registration was skewed toward males but not statistically significant for abandonment. Of 295 registered females, 74 (25.1%) abandoned treatment compared to 108 (20.5%) abandonments among 526 males. In multivariable regression analysis, the type of malignancy, guardian's profession, and travelling from outside the city of Karachi (odds ratio [OR]: 1.48; 95% confidence interval [CI] 1.02–2.15; P = 0.039) correlated with increased abandonment. Treatment abandonment was higher among patients with brain tumors (45.7%) and solid tumors (30.8%) and among those whose guardians were associated with a rural profession (24.7%). Monthly income, age, and number of siblings had no impact on the decision to abandon treatment. Conclusion: Despite the provision of free treatment, the prevalence of abandonment was high. More qualitative data need to be collected to identify and target groups of individuals who may be likely to abandon treatment, thus improving outcome of patients.